Structural and Functional Studies of Phosphoenolpyruvate Carboxykinase from Mycobacterium tuberculosis - Machová, Iva (Public Library of Science, 2015)

(untitled)
Tuberculosis, the second leading infectious disease killer after HIV, remains a top public health priority. The causative agent of tuberculosis, Mycobacterium tuberculosis (Mtb), which can cause both acute and clinically latent infections, reprograms metabolism in response to the host niche. Phosphoenolpyruvate carboxykinase (Pck) is the enzyme at the center of the phosphoenolpyruvate-pyruvate-oxaloacetate node, which is involved in regulating the carbon flow distribution to catabolism, anabolism, or respiration in different states of Mtb infection. Under standard growth conditions, Mtb Pck is associated with gluconeogenesis and catalyzes the metal-dependent formation of phosphoenolpyruvate. In non-replicating Mtb, Pck can catalyze anaplerotic biosynthesis of oxaloacetate. Here, we present insights into the regulation of Mtb Pck activity by divalent cations. Through analysis of the X-ray structure of Pck-GDP and Pck-GDP-Mn2+ complexes, mutational analysis of the GDP binding site, and quantum mechanical (QM)-based analysis, we explored the structural determinants of efficient Mtb Pck catalysis. We demonstrate that Mtb Pck requires presence of Mn2+ and Mg2+ cations for efficient catalysis of gluconeogenic and anaplerotic reactions. The anaplerotic reaction, which preferably functions in reducing conditions that are characteristic for slowed or stopped Mtb replication, is also effectively activated by Fe2+ in the presence of Mn2+ or Mg2+ cations. In contrast, simultaneous presence of Fe2+ and Mn2+ or Mg2+ inhibits the gluconeogenic reaction. These results suggest that inorganic ions can contribute to regulation of central carbon metabolism by influencing the activity of Pck. Furthermore, the X-ray structure determination, biochemical characterization, and QM analysis of Pck mutants confirmed the important role of the Phe triad for proper binding of the GDP-Mn2+ complex in the nucleotide binding site and efficient catalysis of the anaplerotic reaction.